(untitled) (International Journal of Innovative Technologies in Economy, 2020)
Issues of supporting the book publishing as an economic activity by a set of statistical indicators are investigated. It is found out that the existing set of statistical indicators does not meet the needs of researchers and practitioners, which is the case of not only Ukraine, but the global book publishing area. The case of the Ukrainian book publishing is taken for analysis to identify core problems faced by this industry. It is emphasized that a comprehensive study of the book publishing industry and presentation of the statistical information with high level of quality and aggregation requires the involvement of new alternative sources of data, of which big data should be highlighted. The component of scientific novelty is that an updated system of statistical indicators is proposed for the first time, with eight modules of sources of statistical information as alternative ones: questionnaires, electronic books, digital libraries, websites of publishers and bookstores, electronic diaries of reading (Goodreads as an example), social networks (Instagram, Facebook, Telegram (open channels)), video hosts (YouTube being the most popular one), and blogs. It is stressed that all the modules of alternative data must be involved for obtaining reliable data, where output data will be processed anew and have direct and reverse links, which will require the use of neural networks with efferent type of links. This statistical support to the book publishing industry is an innovation designed to meet urgent needs of the public and official statistics.